2022
DOI: 10.1371/journal.pone.0274822
|View full text |Cite
|
Sign up to set email alerts
|

Bystanders of intimate partner violence against women and their willingness to intervene: An analysis of secondary data in Spain (2005–2020)

Abstract: Recent decades have seen a growing acknowledgement of violence against women (VAW) as a serious social and public health problem of epidemic proportions. The prevention of VAW and intimate partner violence against women (IPVAW) has become a priority within this context, and includes various prevention strategies such as social participation and helping behaviors. In different countries, conducting research on help-seeking behavior and bystander intervention in cases of VAW is a common practice, but addressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…If society as a whole is to become a better source of support for families experiencing CPV, future research should continue to explore the attitudes held by the general public, following the progress made here and in research on other types of family violence. For example, research on IPV has been addressing this over the past decade, building precisely on the social aspect of the problem and evidencing the need to raise awareness and to intervene with bystanders as well as with practitioners to improve their helping responses (Gracia et al, 2018, 2020; Sánchez‐Prada et al, 2022). Although interest in CPV has increased in recent years, research in this particular area remains relatively scarce.…”
Section: Discussionmentioning
confidence: 99%
“…If society as a whole is to become a better source of support for families experiencing CPV, future research should continue to explore the attitudes held by the general public, following the progress made here and in research on other types of family violence. For example, research on IPV has been addressing this over the past decade, building precisely on the social aspect of the problem and evidencing the need to raise awareness and to intervene with bystanders as well as with practitioners to improve their helping responses (Gracia et al, 2018, 2020; Sánchez‐Prada et al, 2022). Although interest in CPV has increased in recent years, research in this particular area remains relatively scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Curriculum (Box 1) was developed based on extensive literature review 11–22 to ensure that modules were age‐appropriate, relevant and in line with the thinking of the younger generation, who today are so in tune with social media and its nuances. The 2½‐hour curriculum included case studies, videos, and a dedicated time for questions and answers.…”
Section: Methodsmentioning
confidence: 99%
“…Curriculum (Box 1) was developed based on extensive literature review [11][12][13][14][15][16][17][18][19][20][21][22] to ensure that modules were age-appropriate, relevant and in line with the thinking of the younger generation, who today are so in tune with social media and its nuances.…”
Section: Content Creation: Curriculummentioning
confidence: 99%
“…Findings have shown that a considerable number of cases of VAW occur in the presence of bystanders ( Burn, 2009 ; Gracia et al, 2018 ; European Institute for Gender Equality [EIGE], 2020 ; León et al, 2022 ; Sánchez-Prada et al, 2022 ) and suggest the need and relevance for working with these individuals and convert them into “actionists,” active agents of prevention ( McMahon and Banyard, 2012 ; Fenton and Mott, 2017 ; Fenton et al, 2019 ; McMahon et al, 2019 ; Rothman et al, 2019 ). This leads to the development of intervention programs to modify attitudes and beliefs held by bystanders (such as possible sexist attitudes or blaming the victim) and to strengthen their active responses (reactive and/or proactive) toward the victims ( UNWomen, 2015 ).…”
Section: Introductionmentioning
confidence: 99%